Sociological aspects of pregnant woman's body development - Lovrek Seničič, Monika; Major, Gordana; Božič, Josip (Ošetrovateľstvo a pôrodná asistencia, 2021)
Perception of a pregnant woman's body has been changing through time. While women used to wear baggy clothes trying to cover their pregnancy, today it is completely acceptable exposing and showing your naked pregnant body. „Hiding“ pregnancy once in the Western world was a consequence of taboos that the pregnancy reminds of a corporeality and sexual act that caused it. That required from the pregnant woman covering up and withdrawal from society until the moment of birth. Over time perspective of the body's pregnancy visibility has completely changed. Today, following the example of the world's starlets, every pregnant woman wants a print of her belly in plaster, photos that mark the growth of her belly from day to day. The first 3 months were considered and still are considered a period when the fetus is particularly sensitive and a miscarriage is more likely to occur. Today in the age of social networks, women announce their pregnancy to everyone immediately after the appearance of a small blue plus on the test. In this paper, it will be shown what changes in the body pregnant women encounter throughout the pregnancy, from the very beginning to childbirth.
Keywords: ženy; lidské tělo; Women; Physiology; Pregnancy; fyziologie; Human Body; těhotenství